2022
DOI: 10.1101/2022.09.04.506514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cilialyzer – a freely available open-source software for a standardised identification of impaired mucociliary activity facilitating the diagnostic testing for PCD

Abstract: Background and Objective: Primary ciliary dyskinesia (PCD) is a rare genetic disorder causing a defective ciliary structure, which predominantly leads to an impaired mucociliary clearance and associated airway disease. As there is currently no single diagnostic gold standard test, PCD is diagnosed by a combination of several methods comprising genetic testing and the examination of the ciliary structure and function. Among the approved diagnostic methods, only high-speed video microscopy (HSVM) allows to direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Image stabilization and motion extraction features may have improved signal quantification; Schneiter, et al demonstrated the importance of image stabilization in a freshly excised group of nasal epithelial cells exhibiting a superposed quasi-periodic motion on the ciliary function within the ROI [20]. This resulted in an inaccurate reading of the average power spectral density, which compromised both the display of the CBF-bandwidth, and the actual CBF peak value.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Image stabilization and motion extraction features may have improved signal quantification; Schneiter, et al demonstrated the importance of image stabilization in a freshly excised group of nasal epithelial cells exhibiting a superposed quasi-periodic motion on the ciliary function within the ROI [20]. This resulted in an inaccurate reading of the average power spectral density, which compromised both the display of the CBF-bandwidth, and the actual CBF peak value.…”
Section: Discussionmentioning
confidence: 99%
“…Before analyzing the frequency, the ROI was manually selected using the cropping function. For Cilialyzer, the RAW format video files were converted into sequence images in portable network graphics (PNG) format and pre-processed as stated by the Cilialyzer manual [20]. The preprocessing methods included initial manual image rotation, selecting ROI, image stabilization, cropping margins, and motion extraction.…”
Section: Software Analysismentioning
confidence: 99%
See 3 more Smart Citations